Real-time continuous glucose monitoring in preterm infants (REACT): an international, open-label, randomised controlled trial - Beardsall, K; Thomson, L; Guy, C; Iglesias-Platas, I; van Weissenbruch, MM; Bond, S; Allison, A; Kim, S; Petrou, S; Pantaleo, B; Hovorka, R; Dunger, D; et al. (Elsevier, 2021)
Background Hyperglycaemia and hypoglycaemia are common in preterm infants and have been associated with increased risk of mortality and morbidity. Interventions to reduce risk associated with these exposures are particularly challenging due to the infrequent measurement of blood glucose concentrations, with the potential of causing more harm instead of improving outcomes for these infants. Continuous glucose monitoring (CGM) is widely used in adults and children with diabetes to improve glucose control, but has not been approved for use in neonates. The REACT trial aimed to evaluate the efficacy and safety of CGM in preterm infants requiring intensive care.